2020
DOI: 10.1103/physrevx.10.021031
|View full text |Cite
|
Sign up to set email alerts
|

Realization of a Density-Dependent Peierls Phase in a Synthetic, Spin-Orbit Coupled Rydberg System

Abstract: We experimentally realize a Peierls phase in the hopping amplitude of excitations carried by Rydberg atoms, and observe the resulting characteristic chiral motion in a minimal setup of three sites. Our demonstration relies on the intrinsic spin-orbit coupling of the dipolar exchange interaction combined with time-reversal symmetry breaking by a homogeneous external magnetic field. Remarkably, the phase of the hopping amplitude between two sites strongly depends on the occupancy of the third site, thus leading … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 52 publications
1
77
0
Order By: Relevance
“…Interatomic interactions can be controlled in ultracold gases by means of Feshbach resonances tuned by magnetic fields [143], optically [144], or by tailoring radio-frequency coupled internal states [145]. Density-dependent gauge potentials have recently also been realized [52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interatomic interactions can be controlled in ultracold gases by means of Feshbach resonances tuned by magnetic fields [143], optically [144], or by tailoring radio-frequency coupled internal states [145]. Density-dependent gauge potentials have recently also been realized [52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Only very recently, the first lattice gauge theory [51] within this approach has been put forward, relying on inter-species density-dependent Peierls phases as carriers of the gauge interaction. Recent experimental studies show that such gauge potentials are within reach [52][53][54][55]. Despite this, an issue not yet resolved is how do these density-dependent gauge potentials fit in this classification, provided that they are neither background fields nor do they yield a complete gauge theory per se.…”
Section: Introductionmentioning
confidence: 99%
“…The presented (and rather general) theory paves the way for the experimental detection of chiral currents in trimers of meta-atoms in the latest quantum metamaterials, including with photonic [69][70][71][72] and plasmonic [73][74][75][76] excitations, as well as with circuit QED platforms [77][78][79], clusters of ions [80], and Rydberg [81,82] and ultracold [83][84][85][86] atoms. The tantalizing prospect of the realization of a building block of future non-reciprocal nanophotonic circuitry, such as a circulator or isolator [15][16][17][18][19][20][21][22], is within reach.…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent this problem, different physical effects that mimic the behavior of a magnetic field on charged particles have been proposed including laser assisted tunneling [15], periodic driving [16] or the transfer of angular momentum from light [17]. Recently, in [18] it was demonstrated that spin-orbit coupling in systems of Rydberg atoms can be used to generate Peierls phases in the hopping matrix elements of Rydberg excitations without external light fields, laser assisted tunneling or lattice shaking. The authors showed that the Peierls phases, which are the manifestation of external magnetic fields in lattice models, lead to chiral currents in a triangle-configuration of three atoms.…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper we theoretically investigate a simple one-dimensional extension of the triangle system studied in [18] with density-dependent complex hopping of Rydberg excitations competing with repulsive density-density interactions. Interacting bosons on a lattice in an external effective magnetic field can give rise to a transition between a Meissner and a vortex phase [21][22][23] upon tuning the magnetic flux.…”
Section: Introductionmentioning
confidence: 99%